3D Pseudocontinuous Arterial Spin-Labeling MR Imaging in the Preoperative Evaluation of Gliomas - Zeng, Q; Jiang, B; Shi, F; Ling, C; Dong, F; Zhang, J (American journal of neuroradiology : AJNR, 2017)
Previous studies showed conflicting results concerning the value of CBF maps obtained from arterial spin-labeling MR imaging in grading gliomas. This study was performed to investigate the effectiveness of CBF maps derived from 3D pseudocontinuous arterial spin-labeling in preoperatively assessing the grade, cellular proliferation, and prognosis of gliomas. Fifty-eight patients with pathologically confirmed gliomas underwent preoperative 3D pseudocontinuous arterial spin-labeling. The receiver operating characteristic curves for parameters to distinguish high-grade gliomas from low-grade gliomas were generated. Pearson correlation analysis was used to assess the correlation among parameters. Survival analysis was conducted with Cox regression. Both maximum CBF and maximum relative CBF were significantly higher in high-grade gliomas than in low-grade gliomas ( < .001). The areas under the curve for maximum CBF and maximum relative CBF in distinguishing high-grade gliomas from low-grade gliomas were 0.828 and 0.863, respectively. Both maximum CBF and maximum relative CBF had no correlation with the Ki-67 index in all subjects and had a moderate negative correlation with the Ki-67 index in glioblastomas ( = -0.475, -0.534, respectively). After adjustment for age, a higher maximum CBF ( = .008) and higher maximum relative CBF ( = .005) were associated with worse progression-free survival in gliomas, while a higher maximum relative CBF ( = .033) was associated with better overall survival in glioblastomas. 3D pseudocontinuous arterial spin-labeling-derived CBF maps are effective in preoperative evaluation of gliomas. Although gliomas with a higher blood flow are more malignant, glioblastomas with a lower blood flow are likely to be more aggressive.